2009
DOI: 10.1111/j.1464-410x.2009.08636.x
|View full text |Cite
|
Sign up to set email alerts
|

The aggressiveness of urinary tract urothelial carcinoma increases with the severity of chronic kidney disease

Abstract: had a physical examination (blood pressure), and measurements of laboratory data (serum creatinine, serum haemoglobin) and pathological data. The glomerular filtration rate (GFR) was calculated using the Modification of Diet in Renal Disease equation. Patients were divided into three groups by individual GFR (mL/min), i.e. > 60 (no/mild CKD), 30-60 (CKD stage 3) and < 30 (CKD stage 4/5). RESULTSThe CKD stages included 81 (30.3%) patients with none/mild CKD, 121 (45.3%) with CKD stage 3 and 65 (24.3%) with CKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
2
14
1
2
Order By: Relevance
“…Second, our follow-up period (4 years) might not have been long enough. However, several retrospective studies on UUT- UC patients have shown that the median follow-up period was shorter than 4 years [3,15,16] , so we believe that the findings from our study support the already established speculation that pathological T stage and LVI can function as independent prognostic factors for progression-free and disease-specific survival rates in UUT-UC patients. In our study, 29 patients received adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…Second, our follow-up period (4 years) might not have been long enough. However, several retrospective studies on UUT- UC patients have shown that the median follow-up period was shorter than 4 years [3,15,16] , so we believe that the findings from our study support the already established speculation that pathological T stage and LVI can function as independent prognostic factors for progression-free and disease-specific survival rates in UUT-UC patients. In our study, 29 patients received adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the fact that the exact mechanisms by which relative renal insufficiency leads to UTUC, and possibly to more aggressive UTUC, are unknown, there is some evidence from a population-based cohort study that demonstrates the association between decreased renal function and risk of urinary tract cancer including UTUC [12][13][14]. CKD is common in the elderly population and is suggested as an important risk factor for the development of many cancers including those of the prostate and urinary tract [12].…”
Section: Discussionmentioning
confidence: 99%
“…L'insuffisance rénale chronique au diagnostic pourrait constituer un facteur pronostique de maladie localement avancée [6,17]. Plus cette insuffisance rénale est sévère (clairance de la créatinine < 60 mL/min), plus le risque d'une lésion agressive (stade et grade élevés) est important [17].…”
Section: Facteurs Pronostiques Cliniques En Rapport Avec Le Patientunclassified
“…Plus cette insuffisance rénale est sévère (clairance de la créatinine < 60 mL/min), plus le risque d'une lésion agressive (stade et grade élevés) est important [17]. Cet élément est en défaveur d'un traitement conservateur qui constitue pourtant un impératif de nécessité pour cette classe de patients.…”
Section: Facteurs Pronostiques Cliniques En Rapport Avec Le Patientunclassified